Sub Saharan Challenge Program (SSA CP) Lake Kivu Pilot Learning Site (LKPLS) market baseline survey report - Chiuri, Wanjiku L.; Birachi, Eliud Abucheli (International Center for Tropical Agriculture, 2012)
The main purpose of this report is to give market situational account upon which subsequent efforts will be built to provide efficient marketing systems that work better for smallholder farmers in the LKPLS. Specifically, in this report we give the knowledge of current socio-economic characteristics of traders and an assessment of value chains, access to market information and other market services, existing constraints and opportunities for improved market access and diversified agro-enterprises.